DESENVOLVIMENTO DE METODOLOGIA PARA DETECÇÃO DE ANTIOXIDANTES SINTÉTICOS EM AMOSTRAS DE BIODIESEL POR CROMATOGRAFIA LÍQUIDA DE ALTA EFICIÊNCIA COM DETECTOR ELETROQUÍMICO - Dannyelle da Silva e Silva (2023)
The search for energy derived from renewable sources has increased over the years and the use of renewable fuel with as diesel oil has contributed to the growth of the Brazilian market. Biodiesel has low oxidative stability when compared to fossil fuels, being more prone to degradation. An alternative to delay and/or inhibit the oxidation of lipid compounds is the use of substances known as antioxidants. Antioxidants have been evaluated for use in the biodiesel production process, with synthetic ones being the most studied. With a view to solving the biodiesel stability problem, information was sought in the literature for the development of a simple, viable and effective method for the detection of synthetic antioxidants: Butyl-Hydroxyanisole (BHA), Propyl Gallate (PG) and Tert-Butyl -Hydroquinone (TBHQ) simultaneously by the technique of High Performance Liquid Chromatography (HPLC) coupled with UV-Vis and electrochemical detector using vitreous carbon as working electrode without modification and without the need for pre-treatment of the sample. In the method, reverse phase separation was used, with a wavelength of 280 nm for the UV-Vis detector and electrochemical cell, applying a constant potential of +0.8V. As a result, detection limits of 8.16 μg.mL-1 were obtained for the antioxidant PG, 7.19 μg.mL-1 for TBHQ and 7.92 μg.mL-1 for BHA in UV-Vis detection, in electrochemical detection results were 7.96 μg.mL-1 for PG, 7.47 μg.mL-1 for TBHQ and 8.18 μg.mL-1 for BHA. The quantification limits obtained were in the range between 23.95 – 27.25 μg.mL-1 for all synthetic antioxidants in the two detectors used. Recovery studies varied between 95.78% and 101.66% for PG, TBHQ and BHA antioxidants using the UV-Vis detector and between 99.78% and 100.31% for the electrochemical detector. The proposed method showed viability for the simultaneous detection and quantification of synthetic antioxidants in a biodiesel sample, having as its main advantage the absence of pre-treatment of the sample and any type of modification in the working electrode, allowing it to be used in the quantification of antioxidants in samples of biodiesel for monitoring oxidative stability.